A combined cumulative threshold spectra and digital reconstruction analysis reveal structural alterations of microglia within the prefrontal cortex following low-dose LPS administration. (3rd December 2015) - Kongsui, R.; Johnson, S.J.; Graham, B.A.; Nilsson, M.; Walker, F.R.
Highlights: LPS induced sickness behavior including decreased body weight, food intake and locomotor activity. LPS altered the somal but not processes characteristics of microglia in the prefrontal cortex of adult male rats. The results demonstrate the utility of cumulative threshold spectra analysis and digital reconstruction techniques. Abstract: Sickness behaviors have become the focus of great interest in recent years as they represent a clear case of how peripheral disturbances in immune signaling can disrupt quite complex behaviors. In the current study, we were interested in examining whether we could identify any significant morphological disturbances in microglia associated with these sickness-like behaviors in adult male Sprague–Dawley rats. We chose lipopolysaccharide (LPS 100 μg/kg/i.p.), to induce sickness-like behaviors as it is the most well-validated approach to do so in rodents and humans. We were particularly interested in examining changes in microglia within the prefrontal cortex (PFC) as several recent neuroimaging studies have highlighted significant functional changes in this region following peripheral LPS administration. Paraformaldehyde-fixed tissue was collected from animals 24 h post LPS administration and labeled immunohistochemically with an antibody directed to bind to Iba-1, a protein known to be involved in the structural remodeling of microglia. To analyze changes, we have made use of two recently described image analysis procedures. The first is known as cumulative threshold spectra (CTS) analysis. The second involves the unsupervised digital reconstruction of microglia. We undertook these complementary analysis of microglial cells in the both the pre- and infralimbic divisions of the PFC. Our results indicated that microglial soma size was significantly enlarged, while cell processes had contracted slightly following LPS administration. To our knowledge this study is to first to definitely demonstrate substantial microglial disturbances within the PFC following LPS delivered at a dose that was sufficient to induce significant sickness-like behavior.